Pengaruh destination image, electronic word of mouth, dan accessibility terhadap decision to visit wisatawan pada Wisata Alam Gosari Kabupaten Gresik - Ath'af, Syathirotul; Sukaris, Sukaris (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
This research aims to find out how destination image, electronic word of mouth (eWOM), and accessibility influence tourists’ decision to visit Wisata Alam Gosari, Gresik Regency. This research uses research methods with a quantitative approach. Tourists who visit Wisata Alam Gosari, Gresik Regency are the population of this study. The data collection tool uses a questionnaire, with a sample of 150 respondents. In this research, a purposive non-probability sampling technique was used. Descriptive tests, data quality test, classical assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing were used for data analysis in this research. The findings show that destination image, eWOM, and accessibility partially and simultaneously have a significant influence on tourists’ decision to visit Wisata Alam Gosari , Gresik Regency. This means that the more positive the destination image, the more often potential tourists receive positive eWOM and high accessibility, the greater the decision to visit.